Pengaruh Kecerdasan Spiritual Terhadap Pengguna Game Online Kota Palembang - Sahrul Habi; Candra Darmawan; Emi Puspita Dewi (ScidacPlus, 2023)
The purpose of this study was to determine the influence of spiritual intelligence on online game users in sub-district 3-4 ulu, sub-district of opposite ulu 1 palembang 30114. This study used a quantitative research type with a simple linear regression design and this sample consisted of 35 people who had been formulated previously with using the Slovin formula. The results of the research conducted by the authors indicate that there is an influence of spiritual intelligence on online game users in sub-district 3-4ulu, opposite Ulu 1 sub-district, Palembang city, South Sumatra 30114. From the results of the data collection test scores for reliability statistics Cronbach's alpha obtained an average spiritual intelligence value of 0.764 and online games 0.726 and in the normality test using the Kolmogorov Smirnov test, a significant value of 0.200 > 0.05 is normally distributed, also based on the results of the linearity test on the output of the Anova table, the deviation from linearity sig is obtained. is 0.635 greater than 0.05. This means that there is a significant linear relationship between the spiritual intelligence variable (X) and the online game variable (Y). Significant test of homogeneity of variances 0.521 > 0.05 declared homogeneous. Then get an R2 value of 0.095, which means the influence of spiritual intelligence on online games is 9.5%. Based on the results of the analysis and conclusions in the discussion chapter, the authors propose suggestions for teenagers who like to play online games to increase their religious activities instead of playing online games. Such as praying 5 times a day, participating in IRMAS, as well as other positive activities. Based on the research results, it can be synthesized that there is an influence of spiritual intelligence on online game users in the 3-4ulu sub-district, opposite ulu 1 sub-district, Palembang city, South Sumatra 30114 by 9.5%